Journal of Biodiversity & Endangered Species - OMICS International (OMICS International, 2026)
The Journal of Biodiversity & Endangered Species (JBES) is presented with a vision of providing the young talents a platform to encourage them to develop and globalize their skills and talents for the welfare of the society they are associated with and ultimately to the whole world. The Journal also aims to encourage every young talents to pursue research in fields they are interested and also makes every citizen accessible for the new technologies through their innovative ideas and extraordinary thoughts.
Keywords: Biodiversidad; Especies en peligro; Revistas depredadoras; Predatory journals